Assessment of Endothelial Cell Count Changes Post-Yttrium Aluminium Garnet Laser for Posterior Capsular Opacification - Khan, Amna; Abdul Rauf; Muhammad Haroon Sarfraz; Summaya Khan; Taimoor Ashraf; Nazia Iqbal (Pakistan Armed Forces Medical Journal, 2023)
Objective: The study aimed to assess the effect of Neodymium : Yttrium Aluminium Garnet laser (ND:YAG laser) on endothelial cell count loss and anterior segment elements.Study Design: Quasi-experimental.Place and Duration Of Study: Armed Forces Institute of Ophthalmology, Rawalpindi from Jul 2021 to Feb 2022.Methodology: A total of 60 patients with a history of posterior capsular opacities planned for Neodymium: Yttrium Aluminium Garnet laser posterior capsulotomy were included. Specular microscopy was done pre and post-laser to study and parameters such as central corneal thickness, endothelial cell count, intra-ocular pressure was noted. Data were analyzed by using the Statistical Package for the Social Sciences version 23 softwareResult: After four weeks of Neodymium : Yttrium Aluminium Garnet laser, there was no significant change in the intraocular pressure (p=0.334), however, the visual acuity improved from 0.6±0.3-0.05±0.1 (p